Answer:
x=3
Step-by-step explanation:
9x+63=100
9x+0=27
9(3)=27
Answer:
(-1, 1)
Step-by-step explanation:
Midpoint formula: (x₁ + x₂/2 , y₁ + y₂/2)
Substitute the values into the formula.
(-5 + 3/2 , 3 - 1/2)
(-2/2 , 2/2)
(-1,1)
Therefore, the midpoint is (-1, 1).
Answer:
25 in
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality<u>
</u>
<u>Trigonometry</u>
[Right Triangles Only] Pythagorean Theorem: a² + b² = c²
- a is a leg
- b is another leg
- c is the hypotenuse<u>
</u>
Step-by-step explanation:
<u>Step 1: Identify</u>
Leg a = 24
Leg b = 7 in
Leg c = <em>x</em>
<em />
<u>Step 2: Solve for </u><em><u>x</u></em>
- Substitute in variables [Pythagorean Theorem]: 24² + 7² = x²
- Evaluate exponents: 576 + 49 = x²
- Add: 625 = x²
- [Equality Property] Square root both sides: 25 = x
- Rewrite/Rearrange: x = 25
Answer:
51 + 29
Step-by-step explanation:
Answer:
284.625
Step-by-step explanation:
Arrange the numbers highest to lowest.
Find the middle value in the arrangement.